(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2022)
Background: Plant derivatives with purported hypoglycemic properties have been used in traditional medicine around the world. The Leaves of Cestrum nocturnum (Raat rani) were reported to have good medicinal values in traditional system of medicine. In the present study, we investigated the phytochemical, pharmacological and acute toxicological properties of the extracts of Cestrnumnocturnumleaves. Material and Methods: Antidiabetic effect of hydroalcoholic extract and saponin fraction of Cestrum nocturnum leaves were evaluated in streptozotocin induced diabetic rats. The hydroalcoholic extract 200, 400 mg/kg and saponin fraction 50, 100 mg/kg was administered orally to streptozotocin induced diabetic rats for a period of three weeks. Various biochemical parameters such as blood glucose, lipids, creatinine, urea, alkaline phosphatase, total protein, albumin and liver glycogen content were evaluated. These stated parameters in the diabetic rats were reverted back approximately near to normal after treatment with the respective higher dose of leaf extract and saponin fraction of Cestrum nocturnum. Histological examination of the pancreas from diabetic rats showed degenerative changes in β-cells; whereas treatment signiﬁcantly reversed the histoarchitectural damage to the islets cells. Conclusion: The results obtained in this study indicated that the hydroalcoholic extract and saponin fraction of Cestrum nocturnum leaves significantly improved the levels of various biochemical parameters. The findings could justify the role of this plant material in the management of diabetes. This property of the plant may be attributed to its antihyperlipidemic and hepatoprotective property.